Recent progress in tuberculosis diagnosis: insights into blood-based biomarkers and emerging technologies - Yang, Zewei; Li, Jingjing; Shen, Jiawen; Cao, Huiru; Wang, Yuhan; Hu, Sensen; Du, Yulu; Wang, Yange; Yan, Zhongyi; Xie, Longxiang; Li, Qiming; Gomaa, Salwa E.; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
Tuberculosis (TB) remains a global health challenge, with timely and accurate diagnosis being critical for effective disease management and control. Recent advancements in the field of TB diagnostics have focused on the identification and utilization of blood-based biomarkers, offering a non-invasive, rapid, and scalable approach to disease detection. This review provides a comprehensive overview of the latest progress in blood-based biomarkers for TB, highlighting their potential to revolutionize diagnostic strategies. Furthermore, we explore emerging technologies such as NGS, PET-CT, Xpert and line probe assays, which have enhanced the sensitivity, specificity, and accessibility of biomarker-based diagnostics. The integration of artificial intelligence (AI) and machine learning (ML) in biomarker analysis is also examined, showcasing its potential to improve diagnostic accuracy and predictive capabilities. This review underscores the need for multidisciplinary collaboration and continued innovation to translate these promising technologies into practical, point-of-care solutions. By addressing these challenges, blood-based biomarkers and emerging technologies hold the potential to significantly improve TB diagnosis, ultimately contributing to global efforts to eradicate this devastating disease.